Intellectual capital, management accounting practices and corporate performance : perceptions of managers - Tayles, Mike; Pike, Richard H.; Sofian, Saudah (Emerald Group Publishing Limited, 2007)
The purpose of the paper was to examine whether, and in what way, managers perceive that the level and shape of intellectual capital (IC) within firms influences management accounting practice, specifically, performance measurement, planning and control, capital budgeting, and risk management. It also explores whether such firms are better able to respond to unanticipated economic and market changes and achieve relatively higher performance within their sector. Design/methodology/approach - The paper is based on the results of a study conducted in Malaysia through a questionnaire survey in 119 large companies with varying levels of IC and selected interviews with both accounting and non-accounting executives in a subset of them. Findings - The findings in the paper suggest some evolution in management accounting practices for firms investing heavily in IC. The findings are discussed and further explored through interviews in some of the firms analysed. Research limitations/implications - The limitations of survey research in this paper are acknowledged, however these are ameliorated by confirmatory insights from the interviews. Further research could be carried out using more extensive case studies in companies, perhaps longitudinally, or undertaken using sector focused surveys. Practical implications - It is important to show in the paper that management accounting systems reflect the strategic orientation of the companies concerned. Where a greater focus on intangibles and intellectual capital occurs it may require a different emphasis on management accounting practices compared to companies where they do not feature strongly. It is important that management recognise and act on this in order to improve corporate performance. Originality/value - The paper shows that it is widely recognised that (IC), whether in the form of knowledge, experience, professional skill, good relationships, or technological capacity is a major source of corporate competitive advantage. Whilst the literature places considerable attention on the valuation, measurement and reporting of IC for external reporting purposes, far less attention has so far been given to the implications of IC for managerial accounting practice. This paper addresses this omission.